Cu(In, Ga)Se2 solar cell with 16.7% active‐area efficiency achieved by sputtering from a quaternary target. Issue 8 (13th March 2015) - Ouyang, Liangqi; Zhuang, Daming; Zhao, Ming; Zhang, Ning; Li, Xiaolong; Guo, Li; Sun, Rujun; Cao, Mingjie
<x xml:space="preserve">Abstract</x> In this work, we report the fabrication method of sputtering from a CIGS quaternary target to obtain high‐efficiency CIGS thin‐film solar‐cell devices. The as‐deposited CIGS absorbers are prepared by sputtering from a CIGS target and a subsequent annealing treatment under the Ar + H2Se (5% H2Se) atmosphere is applied on the absorbers. A high conversion efficiency of 16.7% is achieved with an average conversion efficiency of 15.9% over 10 cm × 10 cm on soda‐lime glass. This result shows sputtering directly from a quaternary CIGS target is a very promising fabrication method to obtain high‐performance solar‐cell devices and is suitable for the further fabrication of large‐area devices and modules. <inline-graphic xlink:href="ark:/27927/pgj2dckcrxm" content-type="pssa201532005-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> J–V characteristic curve of the CIGS solar cell with the best efficiency achieved by sputtering from a quaternary target.